Factors for selective ultrasound screening in newborns with developmental dysplasia of the hip (DDH) - Angsanuntsukh, Chanika; Patathong, Tanyaporn; Klaewkasikum, Krongkaew; Jungtheerapanich, Witoon; Saisongcroh, Tanyawat; Mulpruek, Pornchai; Woratanarat, Patarawan (Frontiers in Surgery, 2022)
Background: Hip ultrasound screening for DDH provides better sensitivity compared to physical examination. Due to a lower prevalence and limited resources, selective hip ultrasound in newborns at risk could be considered a proper screening protocol in Thailand and Asian countries. Objective: This study aimed to evaluate risk factors and define criteria for selective screening. Methods: A case-control study was conducted in 2020. All newborns with hip ultrasound screening were included. Cases were defined as newborns with abnormal hip ultrasounds, while controls were those with normal studies. Inter and intra-rater reliability were evaluated. All factors were analyzed using univariate and multivariate logistic regression. The model performance was tested by Hosmer-Lemeshow goodness of fit. Internal validity was performed by the split data method. Results: Ninety-five newborns (29 cases and 66 controls) were included. Eighty percent of cases and 58% of controls were female. The gestational age was 36.6 and 37.7 weeks in case and control, respectively. Female, breech presentation, positive Ortolani’s test, positive Barlow test, and limited hip abduction were significant factors with odds ratio of 2.82, 5.12, 34.21, 69.64, and 5.48, respectively. The final model included breech presentation, positive Ortolani’s test, and positive Barlow test. The model cut-off was 15.02. Sensitivity and specificity were 93.10% and 80.30%, respectively. The area under the ROC was 0.9308. Conclusion: Careful history taking and physical examination are essential to identify the risk factors for DDH. Newborns with breech presentation, positive Ortolani’s test and positive Barlow test should be screened by hip ultrasound.